HUBUNGAN KOMPETENSI DAN BEBAN KERJA DENGAN PRESTASI KERJA GURU MILITER AKADEMI TNI - Elyah Musarovah (Jurnal Manajemen Pendidikan, 2015)
The purpose of this studyis to improve competence and standaritation of workload militery teacher in TNI Militery Academy in Magelang Central Java. The reserch metodology was survey which selected by sample random sampling technique with quesioner. Analysis and interpretation of the data indicates that (1) ability the militery teacher include indicator the competence techer with pedagogik, profesional, attitute and social, (2) workload include all of the militery teacher of the appricial performance with the compentency job and (3) job performance include indicator the quantity, quality, dicipline and attitude performance.